Upaya Meningkatkan Kemampuan Pemahaman Membaca Permulaan dengan Menggunakan Model Belajar Picture and Picture pada Kelas II Sekolah Dasar - Sulis Rahmawati; Ibnu Muthi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Beginning reading skills are a foundational aspect of literacy development in elementary school students, particularly in the lower grades. However, field observations reveal that many second-grade students still struggle with understanding reading materials, recognizing syllables, and associating words with meaning. This study aims to examine the effectiveness of the Picture and Picture learning model in improving reading comprehension skills through a literature review approach. Data were collected from various sources, including literature, journals, and previous research that discussed beginning reading skills and the implementation of image-based learning models. The results indicate that the Picture and Picture model can enhance students’ interest, active participation, and comprehension of texts through engaging and contextual visual support. Images serve as a bridge between text and meaning, helping students to understand story sequences, identify characters, and develop vocabulary and logical thinking skills. Several previous studies analyzed in this research also demonstrated significant improvement in students’ reading abilities following the implementation of this model. Moreover, the model supports an enjoyable learning process, facilitates group collaboration, and builds students’ confidence in expressing ideas. Therefore, the Picture and Picture model is considered effective for use in early reading instruction in elementary schools, especially in creating an active, creative, and meaningful learning environment. This study is expected to serve as a reference for teachers in selecting appropriate teaching strategies to improve students' basic literacy